2007
DOI: 10.2471/blt.06.029389
|View full text |Cite
|
Sign up to set email alerts
|

Vector control complements mass drug administration against bancroftian filariasis in Tirukoilur, India

Abstract: Objective To determine the role of vector control in further decreasing the transmission of bancroftian filariasis achieved by mass drug administration and the long-term impact on filariometric indices. Methods Three rounds of annual mass drug administration, with diethylcarbamazine and ivermectin, were complemented by vector control (mainly using polystyrene beads) in villages of Tirukoilur, south India, during 1995-99. Subsequently, drug administration is being carried out with diethylcarbamazine and albenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…On the other hand, including vector control would essentially, by reducing the hysteresis loop, increase the re-emergence Mf prevalence threshold. This result supports empirical evidence (73) that vector control will be crucial to the long-term sustenance of parasite elimination from treated endemic communities.…”
Section: Modeling the Strategic Importance Of Vector Control In Lymphsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, including vector control would essentially, by reducing the hysteresis loop, increase the re-emergence Mf prevalence threshold. This result supports empirical evidence (73) that vector control will be crucial to the long-term sustenance of parasite elimination from treated endemic communities.…”
Section: Modeling the Strategic Importance Of Vector Control In Lymphsupporting
confidence: 79%
“…Vector control continued in the three villages where it was previously carried out. Analysis in 2006 (73) showed that vector density decreased significantly in villages where vector control was used as an adjunct to MDA, and no infective mosquitoes were found in the small numbers caught during [2003][2004][2005] (82). In the areas where vector control alone interrupted filariasis, facilitation was the vectorparasite relationship involved (72,79).…”
Section: Empirical Field Evidence For the Impact Of Vector Control Onmentioning
confidence: 99%
“…35,36 However, our study quantifies the effect of the most widely implemented vector-control measure, the use of insecticide-treated bed nets. Although vector control is not currently a part of the global strategy to eliminate lymphatic filariasis, universal bed-net distribution is now used widely for malaria control-and-elimination efforts in Papua New Guinea and sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic filariasis (LF) is a major cause of acute and chronic morbidity among humans causing socio economic problems in the tropical and sub-tropical areas of Asia, Africa, the Western Pacific and some parts of the Americas with an increasing prevalence worldwide (WHO 1992, Sunish et al 2007. The uncontrolled population growth, particularly in developing countries of Asia, Africa and Latin America has caused the deterioration of the ecology and environment.…”
Section: Introductionmentioning
confidence: 99%